Creating a Playable Academic Edition of Mourning Dove's Cogewea or How Games can Decolonize. Issue 1 (27th February 2019) - Humphreys, Sara
Digital games have the tools and capacity to build interactive worlds that can both share knowledge and decolonize. Even though games have been accused of reinforcing white supremacist systems that tend to privilege profit over humanity, digital games by Indigenous and Indigenist artists and scholars provide evidence that games have the tools to facilitate decolonization. Along these lines, this paper is an exploration of how digital games can help to decolonize and reframe how Indigenous literature is read in the postsecondary classroom, specifically academic editions of Indigenous literatures.